2020
DOI: 10.4193/rhin19.301
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effects of intralymphatic pollen-specific immunotherapy on Japanese cedar pollinosis

Abstract: Background: Intralymphatic immunotherapy (ILIT) for allergic patients requires only a few intralymphatic injections of the allergen. However, the effectiveness and safety for Japanese cedar pollinosis are unclear. The objectives of this study were to clarify whether and how long ILIT is effective for pollinosis, and its safety. Methods:In an open pilot investigation followed by a double-blind, placebo-controlled study, patients with Japanese cedar pollinosis received 3 intralymphatic inguinal injections of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(77 citation statements)
references
References 31 publications
(56 reference statements)
0
77
0
Order By: Relevance
“…Full-text screening for eligibility excluded 13 studies. Thirteen studies (11 RCTs and 2 cohorts) were included in the qualitative synthesis (8,9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) of which 10 RCTs were included in the quantitative synthesis (8,(19)(20)(21)(22)(24)(25)(26)(27)(28) . A flowchart of the study selection is illustrated in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Full-text screening for eligibility excluded 13 studies. Thirteen studies (11 RCTs and 2 cohorts) were included in the qualitative synthesis (8,9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) of which 10 RCTs were included in the quantitative synthesis (8,(19)(20)(21)(22)(24)(25)(26)(27)(28) . A flowchart of the study selection is illustrated in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…One RCT (19) and two cohorts assessed perennial ARC patients (9,23) . Three studies assessed only patients with moderate to severe ARC (21,24,27) . Characteristics of the included studies are shown in Table 1.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations